The Experience of Womens’ Self-Efficacy on Successful Breastfeeding - Gytta Affrilia Siswanto; Sri Ratnaningsih (International Journal of Advanced Science and Technology, 2020)
Breast milk is an ideal nutrient for baby’s growth and development, has many benefits on biological and emotional effects on the health of mother and baby. There are many psychological factors that play a role in breastfeeding mothers’ confidence such as normative beliefs, maternal confidence, social learning, and behavioral beliefs about breastfeeding. The objective of this study is to review the evidence associated with the experience of self-efficacy for nursing mothers. This study used a framework from Arskey and O’Malley, Focus review is determined, search for articles with relevant databases (PubMed, Poquest, Wiley and gray literature). Selected relevant studies using inclusion and exclusion criteria, conduct critical appraisal to assess article quality, extract data, compile, summarize and report results. Twenty articles were selected according to the inclusion criteria and had Grade A and B, three themes were found from the results of this study, which are self-efficacy factors, breastfeeding, intervention and outcome self-efficacy. In conclusion, research results from articles used in scoping review, show that most articles are found on psychological factors that play a role in breastfeeding confidence such as normative beliefs, maternal self-confidence, social learning, and behavioral beliefs about breastfeeding. Research has shown that breastfeeding confidence turns out to be one of the most important factors that help mothers continue this practice, work support for breastfeeding has also been found to be an important influence to improve breastfeeding practice.